PROPOSIÇÕES PARA O ENFRENTAMENTO DA CRISE DOS CURSOS DE FORMAÇÃO DOCENTE: O PROGRAMA INSTITUCIONAL DAS LICENCIATURAS DA UMESP - FREITAS, SILVIA PERRONE DE LIMA (2018)
The subject of this qualitative research is the crisis faced by the licenciatura degree generated by the low interest young people have shown in pursuing a teaching profession. The issue which guides the investigation relates to the general comprehension of said phenomenon, particularly the genesis of the crisis and the understanding of why so many resources related to the area of education have been shut down. The aim of this research is to contribute to a reflection on the licenciatura degree and teaching profession by studying the paths chosen by Universidade Metodista de São Paulo, notably the Programa Internacional das Licenciaturas. The theoretical framework for this study can be found in Alves (2013) and Sennett (2004) when they discuss the new social morphology of labor generated by global capitalism and its impact in the teaching profession. Furthermore, the theoretical input of Gatti, Barreto and André (2011) contribute to the debate by analyzing the policies behind the teaching profession and the actions to value teachers for the improvement of the quality of Primary Education. The remaining studies which provide reflections on the matter have been conducted by Fundação Carlos Chagas (2009) and its research on the low attractiveness of the teaching profession. The investigation relied on descriptive case studies referring to the PIL by means of documentary analysis, bibliographic revision and semi-structured interviews with five subjects directly involved in the program. The study has allowed the confirmation of the hypothesis that the crisis faced by the current licenciatura degree is the result of a bigger crisis generated by the capitalist system that reveals itself due to the exacerbated relationship of competitivity, as well as flexible and volatile relationships between time and space which demand faster workers who can cope with the emerging paradigms of an impatient society. Our current times have been taken under perspective, accentuated by a new social morphology of labor brought about by a structure of power and control that affects social and labor relationships and likewise the teaching profession.